POSTPARTUM CONTRACEPTIVE USE IN RURAL BAREILLY - Mahmood, Syed Esam; Srivastava, Anurag; Shrotriya, Ved Prakash; Shaifali, Iram; Mishra, Payal (Indian Journal of Community Health, 2011)
Background: Contraception is an important intervention to reduce burden of unwanted pregnancy and promote healthy living among women. Objectives: To find out the postpartum contraceptive usage and identify the different variables which affect the postpartum contraception among the rural females of Bareilly district. Methods: The cross sectional study was carried out in randomly selected villages of Bhojipura Block of Bareilly district, Uttar Pradesh. All women who had delivered within last one year were interviewed by house to house survey to collect data regarding socio-demographic characteristics and contraceptive use by structured questionnaire. A total of 123 women participated in the study. Chi- square test was used to analyze data. Results: Only 13.8% mothers adopted postpartum contraception. Lack of knowledge (32.5%) and young infant being breastfed (28.5%) were the common reasons of not using any contraceptive method. Contraceptive use was higher amongst females aged less than 30 years and those belonging to middle socioeconomic class and nuclear families. The significant influence of the women’ educational status on utilization of family planning methods was observed (p<0.05). Conclusions: Low percent of postpartum contraceptive use indicates the need for improving awareness among the study population.